2013
DOI: 10.1002/jbm.a.34927
|View full text |Cite
|
Sign up to set email alerts
|

The effect of glycation on arterial microstructure and mechanical response

Abstract: Like engineered materials, an artery's biomechanical behavior and function depend on its microstructure. Glycation is associated with both normal aging and diabetes and has been shown to increase arterial stiffness. In this study we examined the direct effect of glycation on the mechanical response of intact arteries and on the mechanical response and structure of elastin isolated from the arteries. Samples of intact arteries and isolated elastin were prepared from porcine aortas and glycated. The mechanical r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Additionally, while the GOH formulation has been shown to model well the tissue response in physiological strain ranges, the exponential fibre term may not be suitable outside this range, where it appears the collagen fibres transition from exponential to more linear behaviour [76]. A modified strain energy function that emulates the GOH response for moderate strains, but approaches linearity nearer to failure strains may thus be more widely applicable.…”
Section: Limitationsmentioning
confidence: 99%
“…Additionally, while the GOH formulation has been shown to model well the tissue response in physiological strain ranges, the exponential fibre term may not be suitable outside this range, where it appears the collagen fibres transition from exponential to more linear behaviour [76]. A modified strain energy function that emulates the GOH response for moderate strains, but approaches linearity nearer to failure strains may thus be more widely applicable.…”
Section: Limitationsmentioning
confidence: 99%
“…Therefore, it is important to have a better understanding of the mechanical properties of elastin and its alteration in disease, as well as the mechanisms by which elastin is degraded/damaged, influencing the arterial remodeling. To understand the mechanical function of elastin in the arterial wall, purified elastin was obtained and mechanically tested using both uniaxial stretching (Lillie and Gosline 2002; Watton et al 2009; Stephen et al 2013) and biaxial tensile testing methods (Gundiah et al 2007; Zou and Zhang 2009; Zou and Zhang 2012). It has been shown that the elastin network in the thoracic aorta possesses anisotropic mechanical behavior, and it becomes increasingly anisotropic with distance from the heart (Zou and Zhang 2009; Watton et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The cross-linking of collagen fibers increases arterial stiffness but may subsequently lead to arterial remodeling. There is much that remains unknown about how the glycation reaction progresses, how it can be affected, and whether it affects other arterial structures in addition to collagen (Stephen et al 2013b). …”
Section: Glycation Of Arteriesmentioning
confidence: 97%
“…Advanced glycation end products in collagen have been shown to affect mechanical properties of tissue, including arteries and articular cartilage (Aronson 2003;Chen et al 2002;Verzijl et al 2002;Wagner et al 2006;Stephen et al 2013b). Several studies have used collagen-associated fluorescence as an unspecific marker of fluorescent AGE products (Brennan 1989;Bruel and Oxlund 1996;Brownlee et al 1986;Reiser et al 1992).…”
Section: Glycation Of Arteriesmentioning
confidence: 98%